INVESTIGATION OF ADAPTIVE MICRO-PROCESSOR CURRENT PROTECTION OF 6–35 kV - F. A. Romaniuk; A. A. Tishechkin; A. V. Kovalevsky (Наука и техника)
Main indices pertaining to technical updating of adaptive micro-processor current protection of 6-35 kV have been obtained. The calculative experiment has made it possible to determine signal dependences in various protection circuits with double-phase and triple-phase short circuits at the beginning of the protected line. Evaluation of time operation of all stages and protection sensitivity has been carried out.